Impacts of solar photovoltaic systems– a case study of solar users in eight villages in Bangladesh - Mallik Akram Hossain,; , Sanjia Mahiuddin,; Noim Uddin,; Zahidul Islam,; Md. Asraf Uddin, (National Geographical Journal of India, 2024)
Being a fast-growing economy, electricity appears to be one of the key drivers for socio-economic development in Bangladesh. However, access to electricity remains an enduring challenge in the country. Only 42% of the rural households are connected with the national grid electricity in Bangladesh. Adopting solar photovoltaic (PV) systems appears as one of the plausible options to address electricity access challenges in rural areas. While positive impacts of using solar PV systems are widely discussed, detrimental impacts are yet to be well understood – especially in the context of Bangladesh. Contributing to the existing discourse, we have addressed residual challenges of using solar PVs based on our field-based surveys and discussions with users’. Treatment of solar PV systems at the end-of-life, unintentional loss of electricity and surprising behavioural changes by the users are detrimental aspects that were found in this research. These aspects are often overlooked and warn implication for the sustainability of solar PV systems in the long-term. Many of these aspects could be addressed during planning and implementation via awareness building as well as (taking appropriate measures at the end of life of solar PVs by the users.